The «Golden Hall» of the National Museum of the Republic of Tuva as a cultural phenomenon - Mongush, Sholbana K.; Mongush, Mergen A. (The New Research of Tuva, 2021)
The collection of archaeological finds from Arzhan II royal mound (Tuva, Russia) joined the exposition of the Aldan Maadyr National Museum in 2008 and soon became the centerpiece of the museum, permanently exhibited under the title “The treasures of the valley of kings. Royal mound Arzhan II”. The exhibition generated a lot of interest in the Scythian heritage among its numerous visitors, which in turn had a profound impact of the cultural life of the region and even on Tuva’s cultural relations. The article examines the background of the exhibition and its subsequent re-displaying and expansion, including the new 2020 exhibits, such as the genuine anthropological material from a high-profile burial on the grounds of Arzhan II complex (latter half of 7th c. BC). The exposition now includes additional accessories of a full dress. A model of Grave, Arzhan II complex, has been created as a full reconstruction of a funeral rite. The article also provides the statistics of museum visits since 2008, and a separate statistics of the Valley of kings exhibition. The analysis of the impact the exhibition had on Tuva’s cultural life covers a number of new books, other produce, touristic and educational events, theatrical and cultural events, all of which make use of Scythian motifs and imagery.